(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
Instagram (IG) is a tool accessible to all and is noticeable its great potential for dissemination and reach of the most different audiences. Through this social network it is possible that the person who is on the other side of the screen embarks on an adventure of knowledge through the posts with information that arrive in a simple, fun and dynamic way. Within this context, an article aims to reflect on the use of IG as a resource for the scientific dissemination of the extension ist project entitled BioCine: Cinema com Ciência, initiated in the period of the Covid-19 pandemic, which, throughout 2021, exhibited nine feature films and animation films that addressed biological themes, in order to promote scientific debates and disseminate science and biology contents. The IG Insights tool showed the increase in interactions in project posts and their relevance to participants, statistics analysis helped make decisions about the most appropriate scientific dissemination strategies to be used. In 2021, The BioCine Project’s Instagram (IG) had 200 publications, of which 41 had relevance above 30, compared to the 203 followers of the project’s profile. In the analysis of the stories, the maximum reach was 54 followers and adding up all impressions obtained a result of 1,202 views between followers and non-followers. The results presented show that the use of the IG Insights tool impacted the process of scientific dissemination of the extensionist project, increasing both the number of participants and the engagement of publications that had an increase in likes and comments. Soon, it proved to be a way to bring quality scientific knowledge to the most diverse audiences.